A comparative analysis of hypofractionated versus conventional radiotherapy for cervical cancer in a resource-limited setting: a prospective study - Mallum, Abba; Tendwa, Maureen Bilinga; Saidu, Rakiya; Swanson, William; Phan, Paul; Li, Heng; Ngoma, Twalib; Avery, Stephen; Huq, M. Saiful; Akudugu, John M.; Ngwa, Wilfred; Incrocci, Luca; et al. (Frontiers in Oncology, 2025)
IntroductionHypofractionation has potential benefits for cancer patients in low-income countries by reducing treatment duration and resource demands. However, few studies have examined the potential for higher toxicity due to the increased radiation dose per session, particularly in patients with existing health burdens like HIV. This study aimed to evaluate and compare the toxicity profiles of conventionally fractionated radiotherapy (CFRT) and hypofractionated radiotherapy (HFRT) in cervical cancer patients in a low-income setting, facilitating a better understanding of the associated risks and benefits to ensure safe and effective treatment options.MethodsA prospective cohort study was conducted at Inkosi Albert Luthuli Central Hospital (IALCH) in South Africa from March 2022 to March 2023. A total of 107 patients with confirmed cervical cancer were recruited and randomly assigned to either CFRT (n = 54; 50.50 Gy in 25 fractions) with weekly chemotherapy or HFRT (n = 53; 42.72 Gy in 16 fractions). Additionally, both groups received high-dose-rate (HDR) intracavitary brachytherapy, with doses of 18.00-, 21.00-, or 10.00-Gy boost. Clinical data and adverse events were recorded and analyzed, with statistical significance set at p < 0.05.ResultsThe median age at diagnosis was 36.4 (28.2–62.9) years, with 85.0% of patients under 40 years and 86.0% HIV-positive. Most patients in both groups presented with stage IIB and grade II disease. HFRT patients completed radiotherapy significantly faster (median, 35 days) than CFRT patients (median, 62 days) (p < 0.001). Both groups experienced similar rates of gastrointestinal (GI), genitourinary (GU), and skin toxicity, although significant differences were found in GI (p = 0.005) and GU (p = 0.01) side effects. Vaginal stenosis was more common in the CFRT group (51.9%) than in the HFRT group (43.4%). Both groups showed comparable clinical responses, recurrence-free survival, and absence of residual disease within 12 months.ConclusionHFRT (42.72 Gy in 16 fractions) offers comparable outcomes to CFRT (50.50 Gy in 25 fractions) with a shorter treatment duration, making it a feasible option in resource-limited settings.